1997
DOI: 10.1002/(sici)1096-9071(199712)53:4<366::aid-jmv9>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Improved detection of respiratory syncytial virus in nasal aspirates by seminested RT-PCR

Abstract: A seminested RT-PCR for amplification of Respiratory syncytial virus (RSV)-RNA in nasal aspirates has been developed and used to test nasopharyngeal aspirates (NPAs) from 132 infants hospitalized with acute respiratory tract infections during winter epidemics. The results were compared with those obtained by virus isolation in tissue culture and antigen detection with an enzyme-linked immunosorbent assay (Ag-ELISA). RSV-RNA was detected by seminested RT-PCR in 57 of the 59 samples that were positive by virus i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
1
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(24 citation statements)
references
References 22 publications
(18 reference statements)
2
20
1
1
Order By: Relevance
“…From the total of HRSV positive results, 80% (12/15) were obtained from children under six months of age, agreeing with data found in the literature (4,13,23,26). Also it was observed that the number of positive cases of HRSV and ARD decreased significantly with the increase of age (data not shown).…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…From the total of HRSV positive results, 80% (12/15) were obtained from children under six months of age, agreeing with data found in the literature (4,13,23,26). Also it was observed that the number of positive cases of HRSV and ARD decreased significantly with the increase of age (data not shown).…”
mentioning
confidence: 59%
“…RT-PCR followed by nested-PCR has been described as a highly sensitive method for viral detection and a useful tool for HRSV diagnosis (13,22).…”
mentioning
confidence: 99%
“…Despite minor discordance in the culture and RT-PCR results, it is likely, given the increased proportion of virus-positive patients with LRTI, that RT-PCR-positive/culture-negative results were true positives, and that RT-PCR is a more sensitive test, particularly for RSV. This has been reported in a number of other settings, including children suspected to have upper respiratory viral infection, 11 infants hospitalized with acute respiratory tract infections during the winter months, 12 and adults with acute hematological malignancies. 13,14 For example, Van Elden et al 14 retrospectively studied bronchoalveolar lavage (BAL) samples from 43 adults with hematological malignancies and a new abnormality on chest radiograph.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the classical method of virus isolation in tissue culture and antigen detection by ELISA, the technique of nucleic acid amplification allows detection of RSV directly from samples within hours. RT-PCR, nested PCR and semi-nested PCR are used commonly in clinical laboratories (Henkel et al, 1997;Rohwedder et al, 1998;Stockton et al, 1998;Abels et al, 2001;Falsey et al, 2002). PCR involving the synthesis of cDNA followed by two amplification reactions was used successfully in our laboratory and works even with a low number of infectious particles at the time of sample collection due to its high sensitivity.…”
Section: Introductionmentioning
confidence: 99%